Outcome of early and delayed closure of temporary ileostomy in children - Hossain, Arman; Islam, M. Kabirul; Matin, Abdul; Lota, Rozina Akter; Islam, Faridul; Islam, Raihan; Rahman, Sharmin (International Surgery Journal, 2024)
Background: Ileostomy is frequently utilized in the surgical management of various congenital and acquired gastrointestinal conditions, often leading to significant patient morbidities. This study aimed to evaluate the outcomes of early versus delayed closure of temporary ileostomies. Method: A prospective comparative interventional study was conducted at Dhaka Shishu (Children) Hospital from March 2017 to September 2019. A total of 48 patients with temporary loop ileostomies were included based on specific inclusion and exclusion criteria. These patients were randomly divided into two groups: early closure (Group A, n=25) and delayed closure (Group B, n=23). Comparative parameters included wound infection, anastomotic leakage, and incisional hernia, with a follow-up period of 6 months postoperatively. Results: In the early closure group, over 50% of patients were less than 1 month old, while 78.3% in the delayed closure group were aged 2-3 months. The cohort comprised 26 males (54.2%) and 22 females (45.8%). Group A patients had a significantly lower mean weight than group B (p<0.05). The predominant diagnosis in both groups was meconium ileus, followed by volvulus neonatorum, small gut atresia, and typhoid ulcer perforation. Post-closure, the overall wound infection rate was 35.4% (40.0% in group A and 30.4% in group B). Anastomotic leakage occurred in 8.0% of group A and 13.0% of group B. Incisional hernia developed in 4.0% of group A and 13.0% of group B (p=0.388). Mortality rates were 4.0% in group A and 8.7% in group B (p=0.601). Conclusion: Early closure of temporary loop ileostomy appears to be a comparatively safe option with lower morbidity, suggesting it as a viable alternative to delayed closure.